PKM PENYULUHAN PERILAKU MEROKOK PADA MASYARAKAT DI DESA PERKEBUNAN MARPINGGAN 2 - Nurrosidah; Butar-Butar, Khairunnisa (Universitas Aufa Royhan Di Kota Padangsidipuan, 2024)
Smoking behavior is a serious health problem. Indonesia is ranked third with the highest number of smokers in the world. Based on 2018 Riskesdas data, the percentage of smokers over 15 years is 33.8%. The results of the Clean and Healthy Living Behavior (PHBS) survey in Marpinggan 2 Plantation Village, especially the indicator of not smoking at home in the community, showed that 57% of respondents smoked at home. This percentage shows that awareness of not smoking at home is still low. This service aims to educate people about stopping smoking at home. The method used in this service is education by counseling and distributing leaflets, followed by evaluation. Based on the activities that have been carried out, the results show that the community is enthusiastic about the activities. As a result of the evaluation, the community felt that this activity was very useful and could increase knowledge about the dangers of smoking. Distributing leaflets can encourage people not to smoke at home. This activity is an effort to educate the public about the dangers of smoking and make people behave better by quitting smoking. Educational activities need to be increased so that society is healthier.